Challenges of flow‐cytometric estimation of nuclear genome size in orchids, a plant group with both whole‐genome and progressively partial endoreplication. (30th April 2015) - Trávníček, Pavel; Ponert, Jan; Urfus, Tomáš; Jersáková, Jana; Vrána, Jan; Hřibová, Eva; Doležel, Jaroslav; Suda, Jan
Abstract Nuclear genome size is an inherited quantitative trait of eukaryotic organisms with both practical and biological consequences. A detailed analysis of major families is a promising approach to fully understand the biological meaning of the extensive variation in genome size in plants. Although Orchidaceae accounts for ∼10% of the angiosperm diversity, the knowledge of patterns and dynamics of their genome size is limited, in part due to difficulties in flow cytometric analyses. Cells in various somatic tissues of orchids undergo extensive endoreplication, either whole‐genome or partial, and the G1‐phase nuclei with 2C DNA amounts may be lacking, resulting in overestimated genome size values. Interpretation of DNA content histograms is particularly challenging in species with progressively partial endoreplication, in which the ratios between the positions of two neighboring DNA peaks are lower than two. In order to assess distributions of nuclear DNA amounts and identify tissue suitable for reliable estimation of nuclear DNA content, we analyzed six different tissue types in 48 orchid species belonging to all recognized subfamilies. Although traditionally used leaves may provide incorrect C‐values, particularly in species with progressively partial endoreplication, young ovaries and pollinaria consistently yield 2C and 1C peaks of their G1‐phase nuclei, respectively, and are, therefore, the most suitable parts for genome size studies in orchids. We also provide new DNA C‐values for 22 orchid genera and 42 species. Adhering to the proposed methodology would allow for reliable genome size estimates in this largest plant family. Although our research was limited to orchids, the need to find a suitable tissue with dominant 2C peak of G1‐phase nuclei applies to all endopolyploid species. © 2015 International Society for Advancement of Cytometry